2022
DOI: 10.3390/ani12070832
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Rescues Dimethoate Exposure-Induced Meiotic and Developmental Defects of Porcine Oocytes

Abstract: Dimethoate (DT) is an environmental pollutant widely used in agricultural fields and home gardens. Studies have shown that exposure to DT causes reproductive defects in both male and female animals. However, the effects of DT exposure on oocyte maturation and the approach to counteract it are not yet known. Here, we investigated the toxicity of DT on porcine oocyte maturation and the protective effects of melatonin (MT) on DT-exposed oocytes. DT exposure with 1.5 mM partially inhibited cumulus cell expansion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…These results indicated that these key regulatory molecules could help yak cumulus cells maintain autophagy and endocytic activity during development. Recently, some studies have pointed out that the addition of melatonin, trehalose and other substances in vitro contributes to oocyte development (33,34), while EGF, as an important paracrine factor in follicles and a commonly used nutritional supplement in vitro culture, plays a crucial role in regulating cumulus cell growth, oocyte maturation and early embryonic development (19,21,23). To further investigate the function of EGF in the regulation of autophagy and endocytosis of cumulus cells, we detected the expression of related genes and proteins in cumulus cells treated with different concentrations of EGF and gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that these key regulatory molecules could help yak cumulus cells maintain autophagy and endocytic activity during development. Recently, some studies have pointed out that the addition of melatonin, trehalose and other substances in vitro contributes to oocyte development (33,34), while EGF, as an important paracrine factor in follicles and a commonly used nutritional supplement in vitro culture, plays a crucial role in regulating cumulus cell growth, oocyte maturation and early embryonic development (19,21,23). To further investigate the function of EGF in the regulation of autophagy and endocytosis of cumulus cells, we detected the expression of related genes and proteins in cumulus cells treated with different concentrations of EGF and gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Most often than not, users do not make reference to the application guidelines in agriculture and public health operation, non use of personal protective clothing and indiscriminate disposal of pesticides containers, inadequate knowledge and awareness of the inherent dangers of pesticides, and absence of monitoring for pesticides residues on locally consumed food have being identified as additional reasons for the reported toxicity of the compound [13,14]. Interestingly, it has been reported that melatonin protects against meiotic defects induced by dimethoate during porcine oocyte maturation, probably by preventing oxidative stress [15].…”
Section: Introductionmentioning
confidence: 99%